(untitled) (Orfeu, 2020)
This article presents aspects of the different compositional poetics adopted in works premièred in the 2019 concert season of grupo Prelúdio 21. The objectives are to demonstrate the variety of procedures, techniques and resources used in works composed by four among the six members of the group, and to describe general aspects of their creation and of the 21st season, which happened in 2019. In order to tackle the proposed objectives, the four composers selected one of the pieces premièred in 2019 to comment and describe some of the relevant features of their poetics, through a specific methodology for each of the works. Among the different procedures featured in the works we can mention: twelve tone composition, modal writing, klangfarbenmelodie, use of pointilistic textures, aspects of instrumental theatre, characteristic intervallic usage, self-intertextuality, electronic resources and remission to traditional cultures by native peoples. We conclude that, besides the wide compositional output and the participation of renowned interpreters throughout its 21 years of existence, the joint work of the composer-members, who also acted as producers, was decisive for the existence and maintenance of the group´s concert seasons. Thus we hope the collective experience of the 21 years of the group´s joint compositional work, which is arguably unique in the world´s contemporary concert music scene, will encourage the appearance of other similar groups.